Peran OHCHR dalam Kasus Pembunuhan di Luar Hukum dalam Kebijakan Perang Melawan Narkoba Filipina - Dinda Anisa Rakhmawulan; Nuraeni Nuraeni (Universitas Airlangga, 2021)
The Office of the UN High Commissioner of Human Rights is an intergovernmentalhuman rights organization that provides advisory services and technicalcooperation at both the national and regional levels. OHCHR will get involvedif a country experiences obstacles related to human rights. This paper aims toanalyze and describe the role of OHCHR in cases of extrajudicial killings sincethe enactment of the War on Drugs Policy in the Philippines. The author uses aqualitative approach with descriptive methods. The author obtains the requireddata through literature studies and interviews. The results showed that OHCHRhas several roles in its involvement, namely as an actor to communicate withthe government, victims’ families, and other international organizations; as aforum to discuss human rights cases in the regular sessions of the UN HumanRights Council; also as a political resource where countries fight over what theOHCHR have to do to support their positions.